2000
DOI: 10.1111/j.1527-3466.2000.tb00039.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Telmisartan: A Novel, Long‐Acting Angiotensin II‐Receptor Antagonist

Abstract: Telmisartan is a potent, long-lasting, nonpeptide antagonist of the angiotensin II type-1 (AT 1 ) receptor that is indicated for the treatment of essential hypertension. It selectively and insurmountably inhibits stimulation of the AT 1 receptor by angiotensin II without affecting other receptor systems involved in cardiovascular regulation. Very high lipophilicity, a unique feature of telmisartan, coupled with a high volume of distribution, indicate that the compound offers the clinically important advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
184
0
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(197 citation statements)
references
References 43 publications
6
184
0
7
Order By: Relevance
“…In addition, it is an insurmountable drug with respect to its AT 1 receptor attachment, leading to slow dissociation from the receptor and thus prolongation of its effect. 38,39 Telmisartan is highly selective for the AT 1 receptor and has no affinity for the AT 2 receptor. By attaching itself to the AT 1 receptor and leaving the AT 2 receptor free, it exerts a dual effect.…”
Section: Angiotensin Receptor Blockers Vs Angiotensin-converting Enzymentioning
confidence: 99%
“…In addition, it is an insurmountable drug with respect to its AT 1 receptor attachment, leading to slow dissociation from the receptor and thus prolongation of its effect. 38,39 Telmisartan is highly selective for the AT 1 receptor and has no affinity for the AT 2 receptor. By attaching itself to the AT 1 receptor and leaving the AT 2 receptor free, it exerts a dual effect.…”
Section: Angiotensin Receptor Blockers Vs Angiotensin-converting Enzymentioning
confidence: 99%
“…E f f e c t s o f T e l mi s a r t a n a n d Va l s a r t a n o n S e r u m L i p i d P r o f i l e file might be involved in the strong insulin-sensitizing effect of telmisartan (14).…”
Section: T a B L E 4 E F F E C T S O F T E L Mi S A R T A N A N D Vmentioning
confidence: 99%
“…For example, although ARBs vary in their binding affinities in in vitro experiments, the significance of the different binding affinities of the various ARBs has rarely been discussed in in vivo studies. 4,5 In in vitro experiments that studied the angiotensin II time-dependent dissociation of telmisartan, olmesartan, candesartan, Exp3174 (an active metabolite of losartan) and valsartan from membrane components containing human AT 1 receptors, the dissociation rate constant of each ARB was 0.003248, 0.004171, 0.005203, 0.008561 and 0.009946 min À1 , respectively, with corresponding half-lives of 213, 166, 133, 81 and 70 min, respectively. 4 In another study assessing binding to cultured Chinese hamster ovary cells expressing human AT 1 receptors, the dissociation rate constant of olmesartan and telmisartan was 0.0096 and 0.0237 min À1 , respectively, with corresponding half-lives of 65 and 29 min, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In in vitro experiments that studied the angiotensin II time-dependent dissociation of telmisartan, olmesartan, candesartan, Exp3174 (an active metabolite of losartan) and valsartan from membrane components containing human AT 1 receptors, the dissociation rate constant of each ARB was 0.003248, 0.004171, 0.005203, 0.008561 and 0.009946 min À1 , respectively, with corresponding half-lives of 213, 166, 133, 81 and 70 min, respectively. 4 In another study assessing binding to cultured Chinese hamster ovary cells expressing human AT 1 receptors, the dissociation rate constant of olmesartan and telmisartan was 0.0096 and 0.0237 min À1 , respectively, with corresponding half-lives of 65 and 29 min, respectively. 5 Miura et al 6 reported structural differences among ARBs, and these differences may explain why olmesartan can block AT 1 receptors to a greater degree than other ARBs.…”
Section: Introductionmentioning
confidence: 99%